Peran Guru Ilmu Pengetahuan Sosial Dalam Menanamkan Sikap Peduli Sosial Pada Peserta Didik Kelas VIII SMP Negeri 3 Kedungwaru - Shifa Nur’Afrianti; Bagus Setiawan (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2024)
Along with the development of technology and the advancement of the world of education, it has both negative and positive impacts. The negative impact that occurred was that various social problems were still found, specifically at SMP Negeri 3 Kedungwaru. The problem of a lack of social care is a challenge for social studies teachers in particular. In this case, apart from providing teaching regarding understanding, teachers through their role are also required to be able to instill good attitudes and morals in students. One example of a student's caring attitude that is still low is the lack of an attitude of helping or helping each other and a high level of indifference to each other among students. The approach in this research uses descriptive qualitative. The research location is at SMP Negeri 3 Kedungwaru, Tulungagung Regency. The respondents interviewed were 2 social studies teachers, 6 students from class VIII-F and 6 students from class VIII-H. Data collection uses observation, interviews and documentation. The results of this research are that teachers play a very good role in the social studies learning process by integrating social care attitudes into their learning materials, school institutions have clean Friday and infaq programs to help instill social care attitudes in students and there are still some students who have an indifferent attitude and not helping each other.